Texts of the passion : Latin devotional literature and medieval society - Bestul, Thomas H. (Thomas Howard), 1942- (Philadelphia, Pa. : University of Pennsylvania Press, 1996)
In Texts of the Passion, Thomas H. Bestul constructs the literary history of the Latin Passion narratives, placing them within their social, cultural, and historical contexts. He examines the ways in which the Passion is narrated and renarrated in devotional treatises, paying particular attention to the modifications and enlargements of the narrative of the Passion as it is presented in the canonical gospels. Of particular interest to Bestul are the representations of Jews, women, and the body of the crucified Christ. Bestul argues that the greatly enlarged role of the Jews in the Passion narratives of the twelfth and thirteenth centuries is connected to the rising anti-Judaism of the period.
He explores how the representations of women, particularly the Virgin Mary, express cultural values about the place of women in late medieval society and reveal an increased interest in female subjectivity. He argues that the richly detailed and increasingly graphic descriptions of the torments of Christ in the Passion narratives not only indicate a new concern with the problem of representing pain, but can be linked to the rise of judicial torture in the thirteenth century. Throughout Texts of the Passion, Bestul offers an articulate and theoretically informed remapping of the relationship between vernacular and Latin literature in the Middle Ages.
Introduction: methodology and theoretical orientations -- Medieval narratives of the Passion of Christ -- The representation of the Jews in medieval Passion narratives -- Gender and the representation of women in medieval Passion narratives -- The Passion of Christ and the institution of torture -- App. 1. Meditation by Bernard on the lamentation of the Blessed Virgin (Meditacio bernardi de lamentacione beate virginis) -- App. 2. Preliminary catalogue of medieval Passion narratives.
Includes bibliographical references (pages 239-257) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Jesus Christ -- Passion -- History of doctrines -- Middle Ages, 600-1500.; Jesus Christ -- Passion -- History of doctrines -- Middle Ages, 600-1500.; Jésus-Christ -- Passion -- Histoire des doctrines -- 600-1500 (Moyen-Âge); Jésus-Christ -- Passion -- Histoire des doctrines -- 600-1500 (Moyen Âge); Jesus Christ; Jésus Christ -- Histoire des doctrines -- 600-1500 (Moyen âge); Jésus Christ -- Passion, dans la littérature.; Christian literature, Latin (Medieval and modern) -- History and criticism; Devotional literature, Latin (Medieval and modern) -- History and criticism; Literature and society -- Europe -- History; Civilization, Medieval, in literature; Littérature chrétienne latine médiévale et moderne -- Histoire et critique; Littérature de dévotion latine médiévale et moderne -- Histoire et critique; Littérature et société -- Europe -- Histoire; Civilisation médiévale dans la littérature.; RELIGION -- Christian Theology -- Christology; LITERARY CRITICISM -- Medieval; Christian literature, Latin (Medieval and modern); Civilization, Medieval, in literature; Devotional literature, Latin (Medieval and modern); Literature and society; Europe; Lijdensgeschiedenis; Kerk en maatschappij; Littérature et société -- Europe -- Histoire; Littérature chrétienne latine médiévale et moderne; Littérature de dévotion latine -- histoire et critique; 600-1500; Criticism, interpretation, etc; History